Perencanaan Kegiatan Ekstrakurikuler Wajib Pendidikan Kepramukaan di SDN 01 Kromengan Kabupaten Malang - Masaadah Mufarihah; Ersa Rohmatus Sholihah (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2024)
This research aims to describe planning and implementation planning an independent attitude development program for scouts its members and carry out planning and development of independence the vigilant attitude of the scout members. Approach and type of research used qualitative descriptive. The data sources for this research are the school principal, scout leader and students of SDN 1 Kromengan, Malang Regency. Data collection techniques using observation, interviews and documentation with data credibility testing through extended observations, member checks and triangulation. The results of this research are the process of planning scouting activities in developing independence scout members' alert attitude, coaches plan their development independent attitude through integrating attitudes within and designing an attitude habituation program. Assessment to knowing the development of students' independent behavior using behavior assessment and behavior journal.